Risk Factors Associated with Chemotherapy Response in Nasopharyngeal Carcinoma: A Cross-Sectional Study from a Tertiary Referral Center in Indonesia - Valencia, Valencia; Utama, Denny Satria; Widyasari, Fiona (Sriwijaya Journal of Medicine, 2025)
Nasopharyngeal carcinoma (NPC) is a type of cancer commonly found in the head and neck, with the highest incidence in Asia. This study aims to analyze the influence of risk factors on chemotherapy response in NPC patients at Dr. M. Hoesin Hospital Palembang. The sample consisted of 65 NPC patients who underwent chemotherapy during the 2022–2023 period, selected using consecutive sampling. The variables studied include age, gender, histopathological classification, cancer stage, body mass index (BMI), and comorbidities. Chemotherapy response, as the dependent variable, was assessed using the RECIST (Response Evaluation Criteria in Solid Tumors) criteria. Data were collected from patient medical records and analyzed using SPSS software with univariate, bivariate (Chi-Squared test), and multivariate (multinomial logistic regression) analysis. The results showed that comorbidities were significantly associated with chemotherapy response, while age, gender, stage, histopathological classification, and BMI did not show significant relationships. Multivariate analysis indicated that age 30-50 years and stage IVA tended to influence chemotherapy response, although it did not reach statistical significance. In conclusion, managing comorbidities is an important factor in the success of chemotherapy in NPC patients, and this study suggests the need for a more holistic approach to treatment by considering other risk factors that may influence therapy outcomes.